Endovascular Treatment of Hepatic Artery Pseudoaneurysm secondary to an Erosion and Liver Block of Perforated Peptic Ulcer - Yoshida, Ricardo De Alvarenga (2013)
Universidade Estadual Paulista Faculdade de Medicina de Botucatu Department of Surgery and Orthopedics